Seed treatment with chlormequat chloride improves the physiological and biochemical characteristics of Brassica napus L. under salt stress - Maryam Vazayefi; Farid Shekari; Esmaeil Zangani; Aria Dolatabadian; Tibor Janda; Andrea Mastinu (Plant Stress, 2023)
Background: Salinity is a global and increasing problem in agriculture. The response of Brassica napus L. (canola or oilseed rape) to salinity and the possible role of chlormequat chloride (CCC) as a seed primer in improving salt tolerance were investigated in a pot experiment. The experiment consisted of four salinities (0, 0.5, 1 and 1.5 g NaCl kg−1 soil) and four CCC concentrations (0, 250, 500 and 750 mg L − 1) in a complete randomised block design with three replications. Results: Salt stress decreased relative water content (RWC), stomatal conductance, stomatal density, photosynthetic rate, chlorophyll, potassium and calcium content, K/Na, Ca/Na ratio and seed yield, but increased leaf temperature, intercellular CO2 concentration, proline, electrolyte leakage, stomatal area and sodium content. Application of CCC, especially 500 and 750 mg L − 1, improved all measured traits and Ca and K contents. The increase in K and Ca content and the simultaneous decrease in Na content indicate improved ion selectivity in plants treated with CCC. Stomatal density was reduced by salt stress, while higher concentrations of CCC increased the number of stomata, especially in the abaxial part, thus reducing the adaxial/abaxial stomatal number ratio. Reduced stomatal number due to salt stress increased the resistance of canola to salt stress by preventing transpiration rate and can be considered as a stress avoidance and water saving mechanism in canola. There is no significant difference in all measured traits between non-saline and mild saline stress, but seed yield decreased at this stress level compared to the control condition. Conclusion: The results suggest that the application of CCC increased the photosynthetic, physiological, and biochemical attributes and seed yield of canola plants. The data show that 500 and 750 mg CCC L − 1 in saline soils up to 10.5 dS m − 1 can improve yield and physiological parameters of canola.